2020
DOI: 10.2174/1573399815666190702161849
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care in Adults with Type 2 Diabetes Mellitus: A Systematic Review

Abstract: Background: Self-care is essential for the prevention of complications in patients with diabetes, but several authors report that even with health education programs, the incidence of complications in patients with diabetes continues to increase. Objective: We aimed to examine adherence to self-care strategies and the repercussions of adherence on the clinical profiles of individuals with type 2 diabetes. Methods: We performed a systematic review according to the Preferred Reporting Items for Systematic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 59 publications
2
29
0
3
Order By: Relevance
“…Consistent with previous research (Al Johani et al, 2015 ; da Rocha et al, 2020 ; Saad et al, 2018 ), adherence to self-care behaviours was low. A likely explanation, though not tested in the present study, could be patients’ insufficient knowledge about diabetes, the importance of self-care in diabetes, and the lack of focused and effective education about diabetes management.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous research (Al Johani et al, 2015 ; da Rocha et al, 2020 ; Saad et al, 2018 ), adherence to self-care behaviours was low. A likely explanation, though not tested in the present study, could be patients’ insufficient knowledge about diabetes, the importance of self-care in diabetes, and the lack of focused and effective education about diabetes management.…”
Section: Discussionsupporting
confidence: 90%
“…Adherence to self-care behaviours is associated with better glycaemic control and improved quality of life in patients with T2D (Babazadeh et al, 2017 ; Colberg et al, 2010 ; Poolsup, Suksomboon, & Jiamsathit, 2008 ). However, research indicates that adherence to self-care behaviours among patients with T2D is suboptimal (Bonger, Shiferaw, & Tariku, 2018 ; da Rocha, Silva, & Cardoso, 2020 ; Mogre, Abanga, Tzelepis, Johnson, & Paul, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO, education is the cornerstone of diabetes treatment. In fact, education has been recommended as an essential component of promoting good control of diabetes, and studies have shown that education is effective in controlling and treating the disease, and according to studies, proper training can reduce 80% of diabetes complications [11,12]. The Health Belief Model is one of the oldest models of behavior analysis that has been used in numerous studies of health behaviors such as type 2 diabetes mellitus (T2DM) [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO, education is the cornerstone of diabetes treatment. In fact, education has been recommended as an essential component of promoting good control of diabetes, and studies have shown that education is effective in controlling and treating the disease, and according to studies, proper training can reduce 80% of diabetes complications [11][12]. The Health Belief Model is one of the oldest models of behavior analysis that has been used in numerous studies of health behaviors such as type 2 diabetes mellitus (T2DM) [13].…”
Section: Introductionmentioning
confidence: 99%